Pendampingan Digitalisasi untuk Meningkatkan Produktivitas Koperasi dengan Aplikasi Point of Sale di Koperasi Serba Usaha Visiana Bhakti - Maryam, dkk., Siti (E-Coops-Day, 2024)
The assistance provided to the Visiana Bhakti Multi-Business Cooperative aims to increase productivity through the implementation of digitalization. By utilizing information and communication technology, cooperative management can be carried out more effectively and efficiently. Digitalization is expected to improve service quality, speed up business processes, and increase efficiency in cooperative management. To support this, an analysis of the results of observations was first carried out to see the problems experienced by the cooperative. Observation results show that this cooperative has not fully implemented digitalization, especially in shop units which still use manual methods for recording sales, so that errors often occur in preparing financial reports. Based on discussions with the cooperative management, it was agreed that digitalization would be implemented immediately. This digitalization process is going well, especially with the implementation of applications Point of Sale (cashier) at the cooperative. Several areas have been identified that require improvement so that digitalization can run consistently and sustainably, so that cooperatives can continue to develop.